2020
DOI: 10.2533/chimia.2020.225
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electronic Structure of Spectator Oxo Ligands by 17O NMR Spectroscopy

Abstract: Spectator oxo ligands are ubiquitous in catalysis, in particular in olefin epoxidation and olefin metathesis. Here we use computationally derived 17O NMR parameters to probe the electronic structure of spectator oxo ligands in these two reactions. We show that 17O NMR parameters allow to distinguish between doubly-bonded and triply-bonded oxo ligands, giving detailed insights into the frontier molecular orbitals involved in the metaloxo bonds along the reaction pathway. On the one hand, our study shows that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 35 publications
5
7
1
Order By: Relevance
“…Notably, 1' features a highly shielded 22 and therefore low skew value ( = 0.19) which is unexpected for a group 6 oxo species. [28][29] For instance, 2' has a calculated skew value of 0.79 indicating the axially symmetric, sp-hybridized, oxo ligand in line with previous studies on tetrahedral Schrock-type alkylidenes. 28 The model 3' features an even further lowered skew value of −0.25, pointing to its primarily sp 2 -hybridized oxo ligand.…”
Section: Natural Chemical Shift Analysis Of Nmr Parameters Benchmarki...supporting
confidence: 85%
See 2 more Smart Citations
“…Notably, 1' features a highly shielded 22 and therefore low skew value ( = 0.19) which is unexpected for a group 6 oxo species. [28][29] For instance, 2' has a calculated skew value of 0.79 indicating the axially symmetric, sp-hybridized, oxo ligand in line with previous studies on tetrahedral Schrock-type alkylidenes. 28 The model 3' features an even further lowered skew value of −0.25, pointing to its primarily sp 2 -hybridized oxo ligand.…”
Section: Natural Chemical Shift Analysis Of Nmr Parameters Benchmarki...supporting
confidence: 85%
“…Analysis of calculated 17 O NMR parameters: To further substantiate the interplay between basal ligands, we calculated and analyzed 17 O NMR parameters of the oxo ligands in 1' -3' (Figure 7a). [28][29]98 The calculated 17 O NMR parameters and the resulting line shapes vary significantly in the series. Notably, 1' features a highly shielded 22 and therefore low skew value ( = 0.19) which is unexpected for a group 6 oxo species.…”
Section: Natural Chemical Shift Analysis Of Nmr Parameters Benchmarki...mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been used to investigate the spectator-oxo effect 64−66 in olefin metathesis and olefin epoxidation. 67 This study suggested that while the formation of peroxo species in olefin epoxidation is assisted by the development of M−O triple-bonding interactions, the metal-oxo bond in olefin metathesis behaves like a triple bond throughout the reaction. Also in that case, the NMR signature of the oxo-ligand is driven by the relative energy of σand πsymmetric orbitals with respect to the M−O bond, thus capturing the essence of the bonding nature of the ligand (Figure 6d).…”
mentioning
confidence: 98%
“…An M–O triple bond is characterized by an axially symmetric 17 O chemical shift tensor, whereas an M–O double bond shows a nonsymmetric tensor. This approach has been used to investigate the spectator-oxo effect in olefin metathesis and olefin epoxidation . This study suggested that while the formation of peroxo species in olefin epoxidation is assisted by the development of M–O triple-bonding interactions, the metal-oxo bond in olefin metathesis behaves like a triple bond throughout the reaction.…”
mentioning
confidence: 99%